Cissus lombardiana a new name for Cissus ulmifolia (Vitaceae) - Kottaimuthu, Ramalingam; Basu, Muthuramalingam Jothi; Sathiyadash, Kullaiyan; Karthikeyan, Veluswamy (Phytotaxa, 2020)
Cissus Linnaeus (1753: 117) is the most speciose genus in the family Vitaceae and notable for its pantropical intercontinental disjunct pattern (Liu et al. 2013). According to the recent estimate, the genus is known to have 291 accepted species (POWO 2020) and it is widely distributed in tropical regions of Africa, Asia, Australia, Central and South America and Mexico (Wen 2007). The main characters delimiting Cissus from other Vitaceae genera are the well-developed, thick and undivided floral disks, tetramerous flowers, one-seeded berries, and seeds with a long and linear chalaza (Wen 2007). In South America, Cissus is represented by 64 species (Lombardi 2000, 2007, Rodrigues et al. 2014). Amongst C. ulmifolia (Baker 1871: 213) Planchon (1887: 552) that is a later homonym of an Italian fossil taxon Cissus ulmifolia Massalongo (1858: 80). While checking the literature and relevant websites for the availability of any synonyms, we found that C. allenii Croat (1977: 358) and C. serrulatifolia Williams (1962: 375) are listed as heterotypic synonyms of C. ulmifolia in Tropicos (2020) following Nelson (2010). However, C. allenii was synonymized under C. serrulatifolia by most of the workers (Govaerts 1999, Lombardi 2007, Morales 2015, POWO 2020, Raz & Zamora 2020) but C. ulmifolia was treated as a distinct species. So in order to ascertain the taxonomic status, we critically studied the protologues and digital specimens including types of these three species, we found that the characters of C. allenii are well within the range of C. serrulatifolia but C. ulmifolia differs from them by its 4-sided, distinctly winged stem (vs. stem terete, not winged or wingless in C. serrulatifolia) and the fruits ovoid or ovoid–subglobose, smooth (vs. obovoid or subpyriform, lenticellate in C. serrulatifolia). Since no other validly published legitimate name is available for this species (Lombardi 2007, Mota de Oliveira & Jansen-Jacobs 2016, POWO 2020), therefore, the authors propose Cissus lombardiana as a replacement name.